Reading cultures : - Travis, Molly Abel (Southern Illinois University Press, 1998)
Molly Abel Travis unites reader theory with an analysis of historical conditions and various cultural contexts in this discussion of the reading and reception of twentieth-century literature in the United States.Travis moves beyond such provisional conclusions as "the text produces the reader" or "the reader produces the text" and considers the ways twentieth-century readers and texts attempt to constitute and appropriate each other at particular cultural moments and according to specific psychosocial exigencies. She uses the overarching concept of the reader "in "and "out "of the text both to differentiate the reader implied by the text from the actual reader and to discuss such in-and-out movements that occur in the process of reading as the alternation between immersion and interactivity and between role playing and unmasking.Unlike most reader theorists, Travis is concerned with the agency of the reader. Her conception of agency in reading is informed by performance, psychoanalytic, and feminist theories. This agency involves compulsive, reiterative performance in which readers attempt to find themselves by going outside the selfengaging in literary role playing in the hope of finally and fully identifying the self through self-differentiation. Furthermore, readers never escape a social context; they are both constructed and actively constructing in that they read as part of interpretive communities and are involved in collaborative creativity or what Kendall Walton calls "collective imagining".